Reconstitution of the U1 small nuclear ribonucleoprotein particle. - Patton, J R (1987)
Although the U1 small nuclear ribonucleoprotein particle (snRNP) was the first mRNA-splicing cofactor to be identified, the manner in which it functions in splicing is not precisely understood. Among the information required to understand how U1 snRNP participates in splicing, it will be necessary to know its structure. Here we describe the in vitro reconstitution of a particle that possesses the properties of native U1 snRNP. 32P-labeled U1 RNA was transcribed from an SP6 promoter-human U1 gene clone and incubated in a HeLa S100 fraction. A U1 particle formed which displayed the same sedimentation coefficient (approximately 10S) and buoyant density (1.40 g/cm3) as native U1 snRNP. The latter value reflects the ability to withstand isopycnic banding in Cs2SO4 without prior fixation, a property shared by native U1 snRNP. The reconstituted U1 particle reacted with both the Sm and RNP monoclonal antibodies, showing that these two classes of snRNP proteins were present. Moreover, the reconstituted U1 snRNP particle was found to display the characteristic Mg2+ switch of nuclease sensitivity previously described for native U1 snRNP: an open, nuclease-sensitive conformation at a low Mg2+ concentration (3 mM) and a more compact, nuclease-resistant organization at a higher concentration (15 mM). The majority of the U1 RNA in the reconstituted particle did not contain hypermethylated caps, pseudouridine, or ribose 2-O-methylation, showing that these enigmatic posttranscriptional modifications are not essential for reconstitution of the U1 snRNP particle. The extreme 3' end (18 nucleotides) of U1 RNA was required for reconstitution, but loop II (nucleotides 64 to 77) was not. Interestingly, the 5' end (15 nucleotides) of U1 RNA that recognizes pre-mRNA 5' splice sites was not required for U1 snRNP reconstruction.